Is the forum of disaster risk reduction ready?: Disaster preparedness in a community setting - Happy Indah Kusumawati; Sutono Sutono; Sri Setyarini; Bayu Fandhi Achmad; Angela Dwi Hesti Ariningtyas; Istighfarlin Widyanita; Syahirul Alim (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
A community-based forum, Forum Pengurangan Resiko Bencana (FPRB), or Forum of Disaster Risk Reduction was established to accommodate and collaborate with stakeholders to optimize disaster management according to local capacity. However, evaluation of disaster preparedness among FPRB members is rarely done. Therefore, this study aimed to determine the disaster preparedness and level of Basic Life Support (BLS) knowledge among FPRB members in Bantul. A descriptive study was conducted with a cross-sectional design. Participants (n=77) were members of FPRB in Poncosari sub-district, Srandakan district, and Girirejo sub-district, Imogiri district, Bantul Regency. The survey was undertaken using the modified Disaster Preparedness Indonesian Institute of Science (LIPI)-UNESCO 2006 questionnaire and modified BLS American Heart Association (AHA) 2015 questionnaire. Univariate analysis was utilized to analyze data. Overall, the majority (52%) of disaster preparedness levels among FPRB members was categorized as strong level (median = 29). Related to the disaster preparedness aspect, 89% had good disaster knowledge, followed by resource mobilization (75%), urgent plan (60%), and early warning (53%). The median score of BLS knowledge was 5.38 (min-max = 2-9). Most of the participants (56%) had a good level of BLS knowledge. This study highlights that the disaster knowledge aspect is indicated as a highly familiar aspect while the early warning aspect is identified as a low familiar one. This study assists policymakers to develop a strategic plan to promulgate further disaster and first aid training in the community setting.